Rethinking the Climate Crisis Here and Now: Mahāyāna Buddhism, Engi Relationality, and the Familiar Pitfalls in Japanese and Taiwanese pro-Nuclear Energy Narratives - NAOFUMI YAMADA; KLARA MELIN; CHING-CHANG CHEN (Czech Journal of International Relations)
Climate inaction occurs partly because the ‘problem’ is often perceived as spatially and temporally distant. Contemporary Japanese and Taiwanese pro-nuclear energy narratives stress the necessity of nuclear energy for solving carbon emissions and energy security issues (here) and the urgency to retain and/or modernize nuclear power generation capabilities (now), despite its known vulnerability. This article deconstructs nuclear energy as a here-and-now solution to the climate crisis, and it proposes Mahāyāna Buddhism as a means to go beyond the modernist beliefs that gave rise to both the climate crisis and the nuclear energy solution. Drawing on Mahāyāna Buddhist thought where subjects are seen as being generated through relations with others (engi) and all beings are inseparable from and intradependent with nature (eshō-funi), we argue that the aforementioned narratives offer a false promise to solve the climate crisis. This is because they ignore the relations between current and future generations, and their techno-national, modernist assumptions reproduce human/nature dichotomies.